(untitled) (Journal of Pedagogical Inventions and Practices, 2022)
Today in our country a lot of attention is paid to the educational process, in particular, the education of students in higher education institutions and the motivation of teachers who teach them. That puts a lot of responsibility on teachers. This article provides examples of non-standard tests recommended for the effective organization of botany classes